Impact Analyses Of Recreational Activities On The Job Satisfaction Of Employees Engaged In Hotel Industry (PUSA Journal of Hospitality and Applied Sciences, 2020)
Background: The hotel industry is known for its long working hours, odd hours such as late  nights and very early morning reporting is very common. Many of them have some particular  problems pertaining to a better maintenance of a work-life balance. Recreational programs  are certain long-term activities that are conducted in an organization which are conducted to  enhance the working and setup of individual behavior and organizational practice which helps  in making certain situation required in improving or maintaining employee physiological,  social and mental well-being. Whereas job satisfaction is the measurement of employee’s  self-motivation and the contentedness with the job. An organization with non-stimulating and  on-thriving workplace cannot attract the qualified and brightest of the bright candidates.Objective: The following research is conducted to help the organization in realizing the  importance of recreational employee engagement activities and their impact on job satisfaction  from employee point of view. Methodology: This is an empirical research and it throws  light on impact of recreational activities on the satisfaction level of employees working in the  hotel industry. The target population include the employees working in the hotel industry at  various grades across Delhi and NCR region. Data collection is done via questionnaires and  previously available researches, internet etc. Results: Out of 140 respondents 97 believes that  recreational activities provide good platform for self-development. Percentage of respondents  agreeing with the fact that activities are effective towards physical and psychological wellbeing  of employees were 73% 48% of the respondents agrees that such activities are a part of  rewards and benefit scheme. All the stress element go away and they can better focus on their  work. Conclusion: As a result of survey done; it came into notice that majority of respondents  believe that recreational activities conducted within the organization creates major impact on  their working environment.
Keywords: Employee Satisfaction; Recreational Activities; Work Life Balance; mployee Engagement